RAILWAY TRANSPORT NAMED AFTER ACADEMICIAN V. LAZARYAN) THE CONTINUOUS TRACK LAYING ON REDEVELOPED LAND CANVAS - Rybkin, V. V.; Patlasov, O. M.; Arbuzov, M. A. (Science and Transport Progress, 2008)
The article presents a method of determination of possibility of laying of long welded track on the repaired ground bed. Such criteria of the ground bed stabilization as stability parameter and stability coefficient are introduced.